INCLUDING DIFFERENCES - Amanda Wiebusch de Amorim, Thays; Elizabeth Kamer Pinheiros, Jane (Revista Gênero e Interdisciplinaridade, 2023)
This study aimed to show inclusion of differences, it is about diversity, about covering everyone, because as human beings we are all different. School Inclusion in recent times is one of the themes that most provokes discussions in the school community. Talking about what inclusion is, differentiating to include, from living with difference to (with) living with difference. School inclusion is a right of all students, with or without disabilities. There are schools that aim to provide equal and quality education to students through a pedagogy of difference, a special look at students. We show a survey where it shows the benefits of inclusion, including is a gain. This work is not intended to reach a conclusion in order to exhaust the subject, but to show that inclusion has many benefits.